2019
DOI: 10.1097/j.pain.0000000000001560
|View full text |Cite
|
Sign up to set email alerts
|

Pain-related functional interference in patients with chronic neuropathic postsurgical pain: an analysis of registry data

Abstract: Although chronic postsurgical pain (CPSP) is a major health care problem, pain-related functional interference has rarely been investigated. Using the PAIN OUT registry we evaluated patients' pain-related outcomes on the first postoperative day, and their pain-related interference with daily living (Brief Pain Inventory) and neuropathic symptoms (DN4: douleur neuropathique en 4 questions) at six months after surgery. Endpoints were pain interference total scores (PITS) and their association with pain and DN4 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 39 publications
4
36
0
3
Order By: Relevance
“…Equivalent to the present study, 11% of all cases and 13% of the thyroidectomy cases in this European study developed CPSP, but thyroidectomy was no risk factor for CSPS at M12. A recent study of the PAIN OUT registry with 2322 patients reported the development of CPSP in 15.3% at M12, but did not include ORL cases 13 . In a cross-sectional survey from 2007 to 2008 in Norway with 2043 participants with surgery 3 months to 3 years preceding the survey, 18.3% reported www.nature.com/scientificreports/ persistent moderate or severe pain 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equivalent to the present study, 11% of all cases and 13% of the thyroidectomy cases in this European study developed CPSP, but thyroidectomy was no risk factor for CSPS at M12. A recent study of the PAIN OUT registry with 2322 patients reported the development of CPSP in 15.3% at M12, but did not include ORL cases 13 . In a cross-sectional survey from 2007 to 2008 in Norway with 2043 participants with surgery 3 months to 3 years preceding the survey, 18.3% reported www.nature.com/scientificreports/ persistent moderate or severe pain 9 .…”
Section: Discussionmentioning
confidence: 99%
“…All pain drugs taken were listed. Finally, German version of the Brief Pain Inventory (BPI) was used to estimate the functional interference within the last 24 h with three domains: physical interference (general activity, walking ability, and work), affective interference (mood, enjoyment of life, and relations with other persons), and sleep was assessed also using 11-point NRS (0 = no impairment; 10 = maximal impairment) 13,29 . Patient with any intensity of persistent pain (NRS ≥ 1) were differentiated from patient with CPSP: All patients who indicated average pain with NRS ≥ 3 at M6 and/ or M12 were defined as patients with CPSP.…”
Section: Methodsmentioning
confidence: 99%
“…This outcome was chosen, as functional interference might be clinically more meaningful and better capture the functional consequences of a chronic pain state. 53 These findings cluster corrected (voxel = 0.005; cluster = 0.05).…”
Section: Methodsmentioning
confidence: 95%
“…sogar mit Opioiden eingestellt sind (z. B. Patienten zum Kniegelenksersatz bei lange vorbestehender Kniegelenksarthrose) [ 31 , 85 ]. Für solche Konstellationen sollten zusammen mit der operativen Abteilung Klinikstandards entwickelt werden.…”
Section: Präoperative Evaluation Und Planung Der Schmerztherapieunclassified